Retrofitting Chinese shophouses: A comparative study in Semarang and Phuket (ARTEKS : Jurnal Teknik Arsitektur, 2025)
This study explores revitalization strategies for Chinese shophouses in the Chinatown areas of Semarang and Phuket, focusing on heritage-based tourism development. This research uses a qualitative descriptive method to examine three main aspects: revitalization, building adaptation through retrofitting, and government policies supporting these transformations. The selected case studies, Tjiang Residence in Semarang and Moh Seng Historical House in Phuket, represent different approaches to preserving cultural heritage while adapting to modern functions. The findings reveal that the Moh Seng Historic House prioritizes the authenticity of architectural and historical values supported by heritage designation. Simultaneously, the Tjiang Residence emphasizes functional optimization for economic purposes without formal heritage recognition. Both cases maintain a Chinese cultural identity through architectural elements and decorative features. The study concludes that successful revitalization strategies balance the preservation of historical character with functional adaptations, enhancing the cultural tourism appeal of heritage districts.
Keywords: Chinese shophouses; Phuket; Retrofitting; Revitalization; Semarang